Exploring the effect of surface chemistry in carbon nanopores on melting behavior of water. (15th November 2021) - Florent, Marc; Rotnicki, Konrad; Przybylska, Natalia; Sliwinska-Bartkowiak, Małgorzata; Bandosz, Teresa J.
Abstract: The trends in the value and shift of a water melting point in nanoporous carbons of distinctive surface chemistry were analyzed. The carbons were obtained from sulfur containing polymers and they were additionally exposed to H2 S at high temperature to introduce specific thiophenic/bisulfides of hydrophobic character. The carbons surface chemistry and porosity were evaluated by XPS, potentiometric titration, thermal analysis and adsorption of nitrogen. The behavior of water was tested using dielectric and tensiometric methods. While carbons had similar sizes of pores, their chemistry differed. The initial carbons were more acidic and more hydrophilic than those H2 S treated. The treatment markedly reduced the surface functionalities from the view point of their chemical character and amount on the surface. As expected for carbon materials, the melting point of water decreased compared to that in the bulk owing to stronger fluid-fluid interactions than those of fluid-walls. Nevertheless, that decrease was smaller for carbons of most acidic surface and thus for those attracting water than for carbons of hydrophobic surface. That apparent discrepancy suggested that roughness, seen in the values of the contact angle and wetting energy, affects melting point more than the low affinity of hydrophobic surface groups to attract water. Graphical abstract: Image 1